2014
DOI: 10.4103/0970-4388.140957
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of instrumentation time and cleaning efficacy of manual instrumentation, rotary systems and reciprocating systems in primary teeth: An in vitro study

Abstract: The reciprocating and the rotary systems showed better cleaning efficacy when compared to manual instrumentation especially, in coronal and middle one third.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 0 publications
7
78
3
8
Order By: Relevance
“…A study performed in primary teeth showed a significant difference in endodontic treatment among three instrumentation techniques (Kfile, ProTaper and WaveOne), mainly with respect to the cleaning of root canals. However, it did not report the possibility of extruded debris around the peri-apex [8]. In a similar manner, did not observe any influence in debris transportation to the periapical region after comparing three preparation techniques [18].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A study performed in primary teeth showed a significant difference in endodontic treatment among three instrumentation techniques (Kfile, ProTaper and WaveOne), mainly with respect to the cleaning of root canals. However, it did not report the possibility of extruded debris around the peri-apex [8]. In a similar manner, did not observe any influence in debris transportation to the periapical region after comparing three preparation techniques [18].…”
Section: Discussionmentioning
confidence: 72%
“…The WaveOne system allows greater flow of irrigating solution by removing smaller amounts of dentin from the channel walls [6], thus reducing the extrusion of debris and reducing the risk of damaging or frustrating the instrument in irregular channels as presented the primary teeth [5][6][7]. This method has also been shown to be more effective in disinfecting the radial channels of deciduous molars [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, rotary instrumentation dramatically reduces the working time, which is a very interesting aspect to consider for pediatric patients (1,(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Cleaning and shaping of the RCS of primary teeth has been traditionally evaluated by destructive methods that do not provide a three-dimensional analysis of the specimens, such as clearing technique, Indian ink injection (3,5,7,8) and serial sectioning into root slices (4). Moreover, two recent studies (9,10) showed the use of computed tomography (CT) in the assessment of root canal preparation of primary teeth.…”
Section: Introductionmentioning
confidence: 99%
“…For the molar deciduous teeth, in the studies comparing the rotary tool system and K type file, the canal shaping performed by rotary tool system was completed faster than the K type, furthermore, it was demonstrated that the rotary tool system enables smoother canal surface and more conical shape, and facilitated the flow of the filling material within the canal (20,21). In their study regarding canal cleansing effectiveness, Katge et al (22) concluded that the rotary tool systems are superior to the preparations performed via K type hand file; while Nazari Moghaddam et al (23) could not find any significant difference between the two.…”
Section: Root Canal Treatment For Deciduous Teethmentioning
confidence: 97%